Gentamicin Applied to the Oval Window Suppresses Vestibular Function in Guinea Pigs - King, E.; Shepherd, R.; Brown, Daniel; Fallon, J. (2017)
Intratympanic gentamicin therapy is widely used clinically to treat the debilitating symptoms of Ménière’s disease. Cochleotoxicity is an undesirable potential side effect of the treatment and the risk of hearing loss increases proportionately with gentamicin concentration in the cochlea. It has recently been shown that gentamicin is readily absorbed through the oval window in guinea pigs. The present study uses quantitative functional measures of vestibular and cochlea function to investigate the efficacy of treating the vestibule by applying a small volume of gentamicin onto the stapes footplate in guinea pigs. Vestibular and cochlea function were assessed by recording short latency vestibular evoked potentials in response to linear head acceleration and changes in hearing threshold, respectively, 1 and 2 weeks following treatment. Histopathology was analyzed in the crista ampullaris of the posterior semi-circular canal and utricular macula in the vestibule, and in the basal and second turns of the cochlea. In animals receiving gentamicin on the stapes footplate, vestibular responses were significantly suppressed by 72.7 % 2 weeks after treatment with no significant loss of hearing. This suggests that the vestibule can be treated directly by applying gentamicin onto the stapes footplate.